PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI KUBIS DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Titis Aditya Handayani; Fembriarti Erry Prasmatiwi; Adia Nugraha (Lampung University, 2020)
This study is to compare the income and technical efficiency of cabbage farming grown in wet landand in rainfed land and to analyse factors influencing the efficiency. The survey was conducted inSumberejo subdistrict of Tanggamus Regency, the center of cabbage production, in January 2019.Respondents wererandomly taken 30farmers who grew cabbagein wet land and 31 who grewcabbage in rainfed land. Data are analyzed quantitatively using income, frontier, andmultipleregression analyses.The results showed that the income of cabbage farming grown in wet land andin rainfed landis different, but they both profitable. There is no difference in the technical efficiency. Factors that influence technical efficiency of cabbage farming grown in wet land and in rainfedland are farming cost (negatively) and farmers’ education level and experience (possitively). Theonly factor influencing technical efficiency of cabbage farming grown in rainfed land is land size.Key words: cabbage farming, income, technical efficiency